Mongodb atlas - Захуцький, В. A. (ХНУРЕ, 2020)
MongoDB Atlas is a aaraoase as a service erearea oy specialists who design and develop MongoDB. It provides ail the features of MongoDB, removing most of the transaction overhead. With MongoDB Atlas, you can quickly deliver your applications and focus on what's important to you and your customers.